China's marine environmental public interest litigation: current situation, challenges, and improvement approach –analysis based on 339 cases - Yang, Lei (Frontiers in Marine Science, 2023)
Marine pollution and ecological damage seriously undermine economic and social development and human life and health and threaten the sustainable development of human society. With the rapid development of industrialization and urbanization and the intense exploitation of marine space and marine natural resources, China’s marine ecology is facing serious problems such as pollution of marine waters, the decline of marine plant and animal resources, and the impairment of the ecological function of coastal zones. China’s marine environmental public interest litigation (MEPIL) has achieved remarkable results in protecting marine natural resources, safeguarding the marine ecosystem, and preventing marine pollution and ecological damage. The paper closely combines the judicial practice of Chinese MEPIL, exploring 339 legal cases brought by administrative organs, public prosecutors, and non-governmental organizations (NGOs) presented on the China Judgment Online from 2018 to 2023. It can be concluded that three modes of MEPIL, namely civil, administrative, and civil public interest litigation incidental to criminal proceedings, have been constructed. Attempts have been made to confirm the standing of the litigation, improve the pre-litigation procedure, and clarify the types of compensation. However, significant obstacles exist in China’s MEPIL. Theoretical clarifications and practical distinctions with other types of proceedings should be made. The current standing should be improved regarding procuratorial organs, administrative authorities, and social organizations. Court jurisdiction systems need to be enhanced. Inconsistencies in the legal provisions on whether MEPIL cases must be under the exclusive jurisdiction of the maritime courts have impeded the efficiency of the handling of cases. The corresponding solutions to the aforementioned obstacles are also analyzed. Clarifying the MEPIL’s nature and improving the relevant laws, and regulations, are essential measures. In addition, providing the explicit interpretation of the legal provisions, expanding the standing, and improving the jurisdictional and other legal system should be explored.